The Relationship Between the Implementation of Hygiene and Sanitation of Street Food in Elementary Schools in Aur Birugo Tigo Baleh District, Bukittinggi City - Yasril, Abdi Iswahyudi; Susanty, Shantrya Dhelly; Adriani, Adriani; Nur, Erdi; Fallen, Ririn Salmi; Rahmat, Andree Aulia (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2026)
Food vendors at elementary schools in Aur Birugo Tigo Baleh sub-district generally still do not meet acceptable personal hygiene and sanitation standards. This can be seen from the vendors' behavior, such as not washing their hands when preparing or serving food, many vendors not using sanitation facilities like aprons, and inadequate sanitation equipment. The purpose of this research is to identify the factors related to the implementation of food sanitation hygiene in the snack foods at the elementary schools in the Aur Birugo Tigo Baleh District, Bukittinggi City, in 2024. This study uses a quantitative method with a cross-sectional study approach. The population in this study consisted of 37 people using the total sampling method. Data analysis used the Chi-square test. The chi-square test results indicate a relationship between attitude and the application of food hygiene and sanitation (p= 0.042; OR= 4.114). Then, 3 variables showed that knowledge (p= 1.000), sanitation facilities (p= 0.495), and environment (p= 0.252) were not related to the application of street food sanitation hygiene. It is hoped that snack food vendors will pay more attention to the hygiene and sanitation of their food, and that health institutions will increase supervision and training for snack food handlers in elementary schools regarding the importance of implementing and improving hygiene and sanitation practices for snack food.